PENGEMBANGAN RPP IPS TENTANG BENTUK INTERAKSI MANUSIA TERHADAP LNGKUNGANNYA YANG MENGINTEGRASI HOTS, LITERASI, PPK, 4C - Putri, Tiara Diah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
implementation of the 2013 curriculum is an effort to improve teacher education standards to reach the national level, namely being able to develop students as a whole in terms of knowledge, attitudes and skills. In the RPP that has been made, it is about analyzing forms of human interaction with the environment and their effects on the social, cultural, and economic development of the Indonesian people which are contained in theme 3, grade 5 SD. This research is a research and development or Research and Development (R&D). Borg and Gall. This study aims to develop an existing lesson plan in which there is learning that integrates HOTS, PPK, literacy, and 4C, and students are able to describe forms of human interaction.